Legal Protection for Buyers in Good Faith in Housing Business Land Disputes - Sulistiyanto, Azareel; Winanti, Atik (Journal of Law, Politic and Humanities, 2025)
Data from Kompas.com showed that throughout 2024, there were a total of 295 cases of land conflicts. The residents of Green Village Bekasi inadvertently became victims of a land dispute due to the unlawful actions of the developer. Therefore, appropriate legal regulations are necessary to protect good faith buyers. This study aims to examine the legal protection afforded to good faith buyers in the property business, as well as the legal protection obtained by the residents of Green Village Bekasi. The research method employed is normative legal research, utilizing statutory and case approaches. The research data were obtained from secondary sources, including primary legal materials, secondary legal materials, and tertiary legal materials. The results of the study indicate that there are no specific laws or regulations explicitly protecting good faith buyers; however, the court, through Decision Number 553/Pdt.Bth/2020/PN Bks, granted legal protection to the third-party objectors by revoking and annulling the Execution Seizure. Furthermore, the residents of Green Village Bekasi deserve recognition as good faith buyers because their transactions fulfill the requirements under the Basic Agrarian Law (UUPA) and Supreme Court Circular Letter (SEMA) No. 4 of 2016